2016
DOI: 10.1177/0899764016651728
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Voluntary Behavior in the Neighborhood Commons

Abstract: The neighborhood commons, and dog parks in particular, provide a good laboratory to explore the drivers of voluntarism and trust, as well as the situational and demographic correlates that promote or inhibit voluntarism. This analysis connects a central theme of Ostrom's work on institutions for overcoming social dilemmas to the literature on voluntary actions and the health of small communities. Survey results from more than 500 users of 14 dog parks in the Atlanta area are examined to understand how variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For example, the National Center for Environment Health of the Centers for Disease Control and Prevention requested that land use planning should consider the effects on public health. 24 Noonan et al 25 found that belonging to a neighborhood was associated with prosocial behaviors. Lenzi et al 26 showed that neighborhood behavioral opportunities and social resources resulted in prosocial behavior in early adolescence.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the National Center for Environment Health of the Centers for Disease Control and Prevention requested that land use planning should consider the effects on public health. 24 Noonan et al 25 found that belonging to a neighborhood was associated with prosocial behaviors. Lenzi et al 26 showed that neighborhood behavioral opportunities and social resources resulted in prosocial behavior in early adolescence.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in a pioneering piece in this strand, Davis and Ostrom (1991) delineate the ways in which institutions and communities can actively produce and provide educational services as a commons, with little differentiation or exclusion among recipients. Other studies in this strand focus on the production and provision of infrastructural services, like decentralised ‘smart’ grids (Araya & Taylor, 2016; Wolsink, 2012) or communally used spaces such as dog parks (Noonan, Matisoff, & Hoelzel, 2016). Environmental protection services (Tompkins & Adger, 2004), care services (Bushouse, 2011), and emergency and housing services (Alford, 2014) are also studied.…”
Section: Elinor Ostrom's Commons Framework and Ostrom‐inspired Commonmentioning
confidence: 99%